Pemanfaatan Ruang Terbuka Hijau di Permukiman Penduduk : Studi Kasus di Kelurahan Pulubala Kota Gorontalo - Irawan, Mohammad Bayu; Frandika K. Toiyo; Sudarmanto Hasan; Suryadi Syamsuddin; Ramli Utina; Dewi Wahyuni K. Baderan (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2025)
The rapid growth of the city in Pulubala Urban Village, Gorontalo City, has resulted in pressure on the environment and the use of green open space (RTH). This study aims to analyse the use of green spaces in the residential area of Pulubala Village, which is inhabited by various ethnic groups. The method applied was descriptive qualitative, with data collection through observation, interviews, and documentation. The research findings indicate that RTH in Kelurahan Pulubala, covering an area of 0.50 Ha, consists of two categories, namely RTH Settlement Area and Smart Park. The benefits of RTH include play areas for children, social activities, and improved environmental quality. However, problems such as lack of space, poor condition, and environmental pollution threaten the sustainability of RTH. To optimise the utilisation of green spaces, better planning, increased public awareness, and the development of attractive facilities are needed. This research is expected to contribute to the preservation and development of green open spaces in urban areas.